Impact of Ion‐Pairing Effects on Linear and Nonlinear Photophysical Properties of Polymethine Dyes. Issue 23 (19th November 2020) - Pascal, Simon; Chi, San‐Hui; Perry, Joseph W.; Andraud, Chantal; Maury, Olivier
Abstract: The two‐photon absorption (2PA) and photophysics of heptamethine dyes featuring cyanine or dipolar electronic structures have been compared for the first time. The perfectly delocalized c yanine system is classically characterized by a two‐photon transition matching the vibronic component of its lower energy absorption band. The dipolar species is generated by ion‐pairing with a hard counterion in a non‐dissociating solvent and displays significant modifications oft he optical properties, including a significant hypochromic shift of absorption, weaker emission and 2PA matching the lower energy transition, thus revealing symmetry breaking within the polymethine electronic structure. Abstract : Size matters : Ion pairing between cationic heptamethine and a small bromine anion in a non‐dissociating solvent results in a symmetry breaking towards a dipolar type chromophore, a transition that is never observed in the presence of a bulky B(C6 F5 )4 anion. For the first time, the effects of ion pairing on the linear and nonlinear photophysical properties is investigated and reveals significant discrepancies between cyanine and dipolar states.